Night and day - Parker, Robert B., 1932-2010 (Parker, Robert B., 1932-2010. Jesse Stone novels., 2009)
Paradise, Massachusetts, Police Chief Jesse Stone must deal in his own laconic way with the town's rights and wrongs, including a Peeping Town, the Paradise Free Swingers, and a firestorm of protests at the junior high school.